The Photon and the Principles of Matter (Global Journal of Science Frontier Research, 2026)
Matter keeps its internal potential-energy (Ep) and sharing-energy (Es) as a (part of a) unity, until being forced out of the unity by external excess-energy (Ee >= Es) as a free particle. Matter shows its sharing-energy (Es) as gravity (F) or weight (W) or inertia-at-rest to its unity centre: Es = F = W. Unity force or inertia (Fu = Es + Ee) is matter's tendency to be unity, expressed as attracting while energy sharing in a unity (Ee = 0), as gravity or weight or inertia-atrest to its unity centre; or repelling while excess-energy transferring out of the unity (Ee → 0), as inertia-in-motion or heat. That is, gravity is redefined as matter's attraction to its unity centre, caused by its sharing-energy. Inertia is redefined and generalised to matter's unity force, caused by its sharing-energy (as inertia-at-rest or gravity) and its excess-energy (as inertia-in-motion or heat). The Big Bang created four kinds of base particles: proton (p), electron (e), neutrino (ν), and photon (γ). The photon tends to be in an electron unity (eγ), oscillating around its electron (the unity centre), attracting while energy sharing. When getting external excess-energy (Ee >= Es), the photon oscillates out of the unity as a free photon (γ + ) with wave-particle duality, leaving the external energy at the speed of light, as a gamma ray, X-ray or light particle, repelling while excess-energy transferring.